Seminal plasma hexosaminidase in patients with normal and abnormal spermograms - Menendez Helman, Renata Julia (2015)
Background: Glycosidases profusion in male reproductive fluids suggests a possible relationship with sperm function. Although Hexosaminidase (Hex) is the most active glycosidase in epididymal fluid and seminal plasma, as well as in spermatozoa, Glucosidase is considered a marker for epididymal function and azoospermia. Objective: The aim of this study was to determine Hex activity in seminal plasma from patients with normal and abnormal spermograms and analyze its correlation with seminal parameters. Materials and Methods: In this cross sectional study, seminal plasma from azoospermic, asthenozoospermic, teratozoospermic, and normozoospermic patients was analyzed for the activity of: total Hex, HexA isoform, and glucosidase. Besides, hexosamine levels were determined, and the amount of Hex was quantified by immunoblot with a specific antibody. Correlation of Hex activity with seminal parameters was also analyzed. Results: Hex activity, like glucosidase, was significantly reduced in azoospermic samples (44, 49, and 60% reduction for total Hex, HexA and glucosidase, respectively). A reduced amount of Hex in azoospermic samples was confirmed by western immunoblot. Hex activity was negatively correlated with round cells in azoospermic samples and positively correlated with motility in asthenozoospermic ones. Conclusion: The results suggested that Hex activity was reduced in azoospermic samples and this was due to a lower amount of enzyme. The correlation to seminal parameters related to particular pathologies suggests a possible relationship of Hex with fertilizing capacity.